Analysis of the Financial Feasibility of Producing an Instant Drink Mixed with Siamese Orange Peel Extract and Cinnamon Extract - Viantika Gea, Anesti; Anggraini, Tuty; Azima, Fauzan (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Instant drinks are now increasingly popular among people. Because its practical use makes it easier for people to consume it. Then, along with the need to maintain health, drinks made from herbal ingredients have also become the people’s choice. One of the herbal ingredients that can be used is Siamese orange peel and cinnamon. The two ingredients are extracted and dried with a spray dryer, and the powder obtained is added with stevia sugar (1:3) and then packaged in 2 grams/sachet. Feasibility analysis is needed to determine whether this instant drink is feasible if used as a production business. From several financial aspects, the Break Event Point (BEP) receipt was IDR 68,480,496, the BEP production volume was 5,707 boxes, and the BEP price was IDR 8,965/box. Then, the eligibility criteria used are Net Present Value (NPV) obtained at IDR 13,049,296 (NPV>0), Internal Rate of Return (IRR) 16.59% (IRR>interest rate), Net Benefit Cost Ratio (Net B/C) 1.23 (Net B/C>1), and Payback Period (PP) 1 year 4 months (PP<age of business).